2016
DOI: 10.1002/jrs.4974
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grafting with acrylate compounds on the conformational rearrangements of silk fibroin upon electrospinning and treatment with aqueous methanol

Abstract: Silk fabrics from Bombyx mori silkworm were grafted with 2‐hydroxyethyl methacrylate (HEMA) as well as a binary system of HEMA and 4‐hydroxybutyl acrylate (HBA) and then analysed by Raman and infrared (IR) spectroscopy to elucidate the interactions between the components and their possible conformational changes. The samples were then dissolved in trifluoroacetic acid and electrospun; the influence of the grafted polymers on the silk fibroin rearrangements upon these treatments was investigated by vibrational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 49 publications
2
13
1
Order By: Relevance
“…As mentioned in the Introduction, crystalline regions of silk fibroin have a prevailing β-sheet conformation and are rich in simple amino acids (Ala, Gly, Ser), while amorphous regions are rich in bulky and polar amino acids [40]. In agreement with previous studies [33], the A 1226 /A 1261 ratio was found to decrease upon grafting, suggesting that the grafted polymer introduced a certain disorder into the fiber; as shown in Figure 7, the ratio well correlates to weight gain for both phosmers. However, it must be observed that A 1226 /A 1261 may also change because of the contribution of the band at about 1255 cm −1 , which is assignable to P=O stretching of the phosphate group [17,43].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…As mentioned in the Introduction, crystalline regions of silk fibroin have a prevailing β-sheet conformation and are rich in simple amino acids (Ala, Gly, Ser), while amorphous regions are rich in bulky and polar amino acids [40]. In agreement with previous studies [33], the A 1226 /A 1261 ratio was found to decrease upon grafting, suggesting that the grafted polymer introduced a certain disorder into the fiber; as shown in Figure 7, the ratio well correlates to weight gain for both phosmers. However, it must be observed that A 1226 /A 1261 may also change because of the contribution of the band at about 1255 cm −1 , which is assignable to P=O stretching of the phosphate group [17,43].…”
Section: Resultssupporting
confidence: 90%
“…Other bands were found to strengthen upon grafting, such as the CH 2 bending mode at about 1450 cm −1 , which also showed an increase of its full-width at half-maximum (FWHM) from 25 cm −1 (control) to 28 cm −1 (grafted samples). Moreover, a new component was detected at 1485 cm −1 , in agreement with the trend observed upon grafting with HEMA [33].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Upon grafting, the fabrics underwent conformational rearrangements towards a more unordered state, although they kept their prevailing β‐sheet conformation. By immersing the as‐electrospun grafted and pure fibroin nanofibres (prevalently unordered) in aqueous methanol, they partially recovered the β‐sheet content observed in the corresponding starting fabrics …”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…By immersing the as-electrospun grafted and pure fibroin nanofibres (prevalently unordered) in aqueous methanol, they partially recovered the β-sheet content observed in the corresponding starting fabrics. [151] 15.5 | Glasses, ceramics, powders, and disordered materials Magyari and co-workers studied the effect of titania on the bioactivity of silicate bioactive glasses. Their investigation demonstrates that the FWHM of the Raman band combined with the FT-IR data recorded in reflection mode can be used as key spectral indicators for elucidating the evolution of apatite-like structures developed on the bioactive material surface.…”
Section: Linear Chains and Polymersmentioning
confidence: 99%